Islamic e-organizer - Abdul Rahman, Marfizah (2001)
The Internet technology become more popular among the people in the world. It included all professionals, teenagers, children and also housewifes. But, the Islamic application are less . Islamic application is needed to make sure our generations get the good knowledge from the Internet. If not, they may use the Internet for the useless things. This project will develop the Islamic E-Organizer. This software is used for people to organize their daily activities using the Islamic way of live. One features to be carry out is the usage of Islamic Calendar. The software will be designed and developed using the ASP software which based on Microsoft IIS technology. The software expected to give challenge to their organizer software which can be found in the Internet.